Implementasi Sistem Pengarsipan Metode Alphabetical, Subject Dan Chronological Filing Untuk Meningkatkan Tata Kelola Arsip PT Tunas Antarnusa Muda Cargo Solo - Nayun Chaledha Zahra; Tasya Widya Sari; Theodora Fausta Ayu Gracia; Binti Muchsini (FKIP, Universitas Palangka Raya, 2023)
Archives play an important role in supporting the administrative activities of an agency. Archives include all activities related to company documents. At the expedition agency PT Tunas Antarnusa Muda Cargo Solo, the receipt document filing system is still lacking in structure. This receipt is only archived to the extent that it is entered in an order that is adjusted to the customer's name randomly and unstructured. This makes employees of PT Tunas Antarnusa Muda Cargo Solo, especially the finance division, find it difficult to find receipts so that work management becomes less effective and efficient due to the long search time when receipts are needed. This service aims to improve the filing system at PT Tunas Antarnusa Muda Cargo Solo by using a combination of alphabetical filing, subject filing, and chronological filing methods. This method is applied in alphabetical order of the customer's name, the subject of grouping the customer's names and sorted by the time the receipt was made. In practice, this method aims to manage receipts to increase the efficiency and effectiveness of the filing system. In addition, structured archives can make it easier for agency employees to find the information needed quickly and simplify the work process